Pengujian Web Pengiriman Pos Indonesia Menggunakan Metode Black Box Boundary Value Analysis - Bagaskara, Dhimas Bintang; Kurniawan, Bagus; Wicaksono, Angger (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2023)
POS Indonesia is one of the logistics platforms in Indonesia. POS Indonesia has a website that can be used to check shipping rates. The method used in testing the POS Indonesia website is to use black-box testing with boundary value analysis techniques. The test is carried out on the Calculate Shipping Rates form by measuring the minimum and maximum limits of the package weight and volume column. This test focuses on several available shipping options such as Special Express Posts, Express Posts, Instant Posts, and Economic Jumbo Posts. This test compares the test results with the delivery characteristics of all types of shipments on the Pos Indonesia website and focuses on the Calculate Shipping Rates section and will test several things such as maximum shipping weight, maximum dimensions of goods, minimum shipping weight, data reset button, and entering letters. on the weight of the goods. The results of this test can be used as input to improve the POS Indonesia website form so that when users use the web to calculate shipments, the data looks clearer and in accordance with the delivery provisions that have previously been made.